Ethical Frameworks and Regulatory Governance: An Exploratory Analysis of the Colombian Strategy for Artificial Intelligence - Thoene, Ulf; García Alonso, Roberto; Dávila Benavides, Diego Eduardo (Law, State and Telecommunications Review, 2024)
[Purpose] This article analyzes the Colombian Artificial Intelligence (AI) Strategy and seeks to answer the formulation process of Colombia’s digital transformation and Artificial Intelligence strategy. [Methodology/approach/design] The study utilizes a case study analysis approach to explore factors that may have influenced the Colombian AI policy formulation process. We conducted an elite interview and documentary research on public policy documents. [Findings]. This study identifies the inherent challenges of the national strategy for artificial intelligence. The implementation of the Colombian AI Strategy is guided by a market-oriented state model that promotes self-regulation regarding AI. [Practical implications] National strategies are an increasingly important theme of scholarly debate in AI policy. This article aims to contribute to analyzing such strategies, including the challenges inherent in their design and implementation. [Originality/value] This article examines how Latin America’s third most populous country, Colombia, shapes AI governance strategies. The uniqueness of this study lies in its proposition to outline the model of AI governance based on a detailed analysis of public policies.